Single-molecule dissection of CFTR folding defects and pharmacological rescue - Sang Ah Kim; Jesper Levring; Jue Chen; Tae-Young Yoon (Proceedings of the National Academy of Sciences, 2026)
Cystic fibrosis is a lethal genetic disorder caused by misfolding of the cystic fibrosis transmembrane conductance regulator (CFTR) protein, most commonly due to the ΔF508 mutation. Despite extensive study, CFTR’s folding process has remained inaccessible to direct observation. Here, we apply single-molecule magnetic tweezers to resolve the complete folding trajectories of wild-type and ΔF508 CFTR with near–amino acid resolution. We find that CFTR follows a hierarchical, template-guided folding pathway in which N-terminal domains scaffold downstream folding. This mechanism tightly couples the free energy states of intermediates, allowing ΔF508-induced instability to propagate across the folding pathway. Pharmacological correctors, in synergy with ATP, reshape the entire folding energy landscape by catalyzing transitions rather than simply stabilizing end states. These long-range, allosteric effects reveal a folding-embedded regulatory network. Our work provides a quantitative framework for mapping multidomain protein folding and therapeutic rescue, offering a broadly applicable strategy for interrogating rare mutations and accelerating structure-based drug discovery.